Mouse Reporter Strain for Noninvasive Bioluminescent Imaging of Cells that have Undergone Cre-Mediated Recombination - Michal Safran; William Y. Kim; Andrew L. Kung; James W. Horner; Ron A. DePinho; William G. Kaelin (Molecular Imaging)
Conditional alleles containing LoxP recombination sites, in conjunction with Cre recombinase delivered by a variety of means, allows for spatial and temporal control of gene expression in mouse models. Here we describe a mouse strain in which a luciferase (Luc) cDNA, preceded by a LoxP-stop-LoxP (L-S-L) cassette, was introduced into the ubiquitously expressed ROSA26 locus. Mouse embryo fibroblasts derived from this strain expressed luciferase after Cre-mediated recombination in vitro. ROSA26 L-S-L-Luc /+ mice expressed luciferase in a diffuse or liver-restricted pattern, as determined by noninvasive, bioluminescent imaging, when crossed to transgenic mice in which Cre was under the control of a zygotically expressed (EIIA-Cre), or a liver-restricted (albumin-Cre), promoter, respectively. Organ-specific luciferase expression was also seen after intraparenchymal administration of an adenovirus encoding Cre. The ROSA26 L-S-L-Luc /+ strain should be useful for characterizing Cre mouse strains and for following the fate of cells that have undergone Cre-mediated recombination in vivo.